Litter Decomposition Rate of Karst Ecosystem at Gunung Cibodas, Ciampea Bogor Indonesia - Sethyo Vieni Sari; Ibnul Qayim; Iwan Hilwan (Journal of Tropical Life Science, 2016)
The study aims to know the productivity of litter and litter decomposition rate in karst ecosystem. This study was conducted on three altitude of 200 meter above sea level (masl), 250 masl and 300 masl in karst ecosystem at Gunung Cibodas, Ciampea, Bogor. Litter productivity measurement performed using litter-trap method and litter-bag method was used to know the rate of decomposition. Litter productivity measurement results showed that the highest total of litter productivity measurement results was on altitude of 200 masl (90.452 tons/ha/year) and the lowest was on altitude of 300 masl (25.440 tons/ha/year). The litter productivity of leaves (81.425 ton/ha/year) showed the highest result than twigs (16.839 ton/ha/year), as well as flowers and fruits (27.839 ton/ha/year). The rate of decomposition was influenced by rainfall. The decomposition rate and the decrease of litter dry weight on altitude of 250 masl was faster than on the altitude of 200 masl and 300 masl. The dry weight was positively correlated to the rate of decomposition. The lower of dry weight would affect the rate of decomposition become slower. The average of litter C/N ratio were ranged from 28.024%--28.716% and categorized as moderate (>25). The finding indicate that the rate of decomposition in karst ecosystem at Gunung Cibodas was slow and based on C/N ratio of litter showed the mineralization process was also slow.